Report on a visit to Niger, 12-25 June 1994 - Abernethy, Charles L. (International Irrigation Management Institute, 1994)
This report describes a short visit made by the writer to the Republic of Niger, 12-25 June 1994. The primary purpose was to review progress in the project PMI-Niger (Irrigation Management Project, Niger) and to offer ides and recommendations for its future stages. PMI-Niger is a collaborative project between the International Irrigation Management Institute (IIMI) and the Government of Niger, and is financed by the African Development Bank.